STRATEGI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN FIQIH KELAS 1 DI MADRASAH IBTIDAIYAH KHADIJAH MALANG - Nur Halimah; Azhar Haq; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This report is in order to figure out how the strategy used teachers in improving the quality of learning fiqih class 1 madrasah ibtidaiyah khadija. Poor this research was done using, data collection techniques of them: observation, interviews and dokumentation. Documentation in this research, researchers used instrument interview to find the problems that have to be researched. At this point, teachers less consistent in using, learning strategy a method of learning, and the media learning so that students to take the matter with well and good. The main causes is teacher less creative and innovative in drawing up lesson plans and develop it using the strategies of learning, a method of learning, and the media. Learning in this case researchers will talk about quality of learning fiqih and strategies to improve teacher quality of learning fiqih one class  in madrasah ibtidaiyah khadija. Related to this, the researchers found the researchers found learning in accordance with maple fiqih one class at the madrassa ibtidaiyah khadija malang such a strategy that centered on students called inkuiri.Which his course has made the students become active and fun in the process of learning. As for a strategy in improving the quality of learning fiqih among them: teachers have to make lesson plans with creative and innovative in order to facilitate students receive, material teachers aware of the purpose of learning, and find sources other than lks.Keywords: Teacher strategy, quality of learning fiqih .